Luteolin, a bioflavonoid inhibits colorectal cancer through modulation of multiple signaling pathways: a review - Pandurangan, Ashok Kumar; Mohd Esa, Norhaizan (Asian Pacific Education Press Ltd., 2014)
Luteolin, 3’, 4’, 5,7-tetrahydroxyflavone, belongs to a group of naturally occurring compounds called flavonoids that are found widely in the plant kingdom. It possesses many beneficial properties including antioxidant, antiinflammatory, anti-bacterial, anti-diabetic and anti-proliferative actions. Colorectal cancer (CRC) is a leading cause of cancer related deaths worldwide. Many signaling pathways are deregulated during the progression of colon cancer. In this review we aimed to analyze the protection offered by luteolin on colon cancer. During colon cancer genesis, luteolin known to reduce oxidative stress thereby protects the cell to undergo damage in vivo. Wnt/β-catenin signaling, deregulated during neoplastic development, is modified by luteolin. Hence, luteolin can be considered as a potential drug to treat CRC.